Lack of Institutional Support in the SAFPI Individual Teaching Process: A Bibliometric Analysis in Scopus Using PRISMA - Jennifer Cristina Cambisaca Sigua; Nathalie Marie Chunir Guzman; Paola Anabel Fernández Cuzco (Asian Journal of Early Childhood and Elementary Education, 2026)
Institutional support is a critical factor in strengthening individualized teaching processes in early childhood education, particularly in family-centered educational modalities such as the Family Care Service for Early Childhood (SAFPI). However, the scientific literature addressing the relationship between institutional support and individualized teaching in this context remains fragmented. This study aims to analyze the scientific production on institutional support in individualized teaching processes in early childhood education through a bibliometric analysis of documents indexed in Scopus. A systematic review with a quantitative, descriptive, and documentary approach was conducted following the PRISMA framework to ensure transparency in study identification, screening, eligibility, and inclusion. The search covered publications indexed between 2021 and 2026 using terms related to institutional support, individualized teaching, early childhood education, family support, and educational management. Scientific articles and reviews relevant to the research focus were included, while duplicate records, irrelevant studies, and documents that did not meet the predefined criteria were excluded. The findings reveal sustained growth in scientific production during the analyzed period, with Australia, the United Kingdom, and the United States showing the greatest research participation. Scientific articles predominated, particularly within the Social Sciences and Humanities, reflecting increasing scholarly interest in the institutional conditions that shape educational provision in early childhood. The synthesis further indicates that institutional support, teacher training, family participation, and administrative management are closely associated with the quality of individualized teaching processes. The study concludes that institutional support constitutes an essential component for strengthening family-centered early childhood education models such as SAFPI. It contributes a bibliometric overview of the field while identifying persistent research gaps in Latin American contexts that warrant greater scholarly and educational attention.